AN ANALYSIS ON THE CHARACTERIZATION OF THE MAIN CHARACTER IN THE PHANTOM OF THE OPERA"™S FILM - Hapsari, Atika; Rosnija, Eni; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractLiterature works come in many forms and types, one of which is films. Films are categorized as forms of drama in which the artistic works are realized through acting. In today"™s society, film industry is one of the most influential sectors of modern society. Among many reasons, film can entertain, educate and inspire viewers in many ways. As one of the elements in a story, characters in films have been the target of literature analysis due to its significance role in the development of a story. Thus, this study aims to analyze the characterization of the main character in the Phantom of the Opera"™s film. The focus on the analysis is on The Phantom himself or known as Erik. This research analyzes how the character of Erik is portrayed in the film through his dialogue and interaction with other characters. The theory that supports this thesis is psychology of literature by Robbert (Jeff) and Paul Costa. This thesis used descriptive qualitative research. The researcher watch the film and read the script, collect the data, analyzed the data, and concluded the data. The findings revealed that the main character has high neuroticism that is the susceptibility to experience negative emotions. The main character showed a lot of negative emotions such as anger, anxiety, frustration, vulnerable, guilt, manipulative, insecure, selfconsciousness, and aggressive.Keywords: Analysis, character analysis, the phantom of the opera